2019
DOI: 10.1002/jcop.22304
|View full text |Cite
|
Sign up to set email alerts
|

If momma ain't happy with the mentoring relationship, ain't nobody happy with the mentoring relationship: Parental satisfaction as a predictor of mentoring match strength and length

Abstract: Much evidence exists on whether an individual's perception of a match relationship impacts match strength and length, but relatively less is known about whether parental perceptions of the match (i.e., whether the match is meeting their goals) impacts the length and strength of mentoring relationships. These relationships were examined in a sample of 350 newly formed youth–mentor matches who completed multiple measures of match strength and satisfaction with the match. Parents/guardians were also surveyed abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
(41 reference statements)
1
9
0
Order By: Relevance
“…Evidence gathered from short- and long-term mentoring programs suggests that for mentoring programs that specifically address parental involvement, the likelihood of early closure is lessened [ 41 ]. Similarly, parent/guardian satisfaction with the mentoring goals in BBBS America mentoring programs predicts match strength and duration, as derived from mentors’ and mentees’ reports, whereas parent/guardian dissatisfaction predicted match closure [ 180 ]. Mentor satisfaction with the mentee’s family regarding the emotional tone of the relationship, communication, cooperation, and appreciation predicted mentors’ satisfaction with the mentoring relationship, even after controlling for organizational support, mentors’ cultural competence, and other personal characteristics in a long-term American program [ 181 ].…”
Section: Resultsmentioning
confidence: 99%
“…Evidence gathered from short- and long-term mentoring programs suggests that for mentoring programs that specifically address parental involvement, the likelihood of early closure is lessened [ 41 ]. Similarly, parent/guardian satisfaction with the mentoring goals in BBBS America mentoring programs predicts match strength and duration, as derived from mentors’ and mentees’ reports, whereas parent/guardian dissatisfaction predicted match closure [ 180 ]. Mentor satisfaction with the mentee’s family regarding the emotional tone of the relationship, communication, cooperation, and appreciation predicted mentors’ satisfaction with the mentoring relationship, even after controlling for organizational support, mentors’ cultural competence, and other personal characteristics in a long-term American program [ 181 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, an interpersonal history of poor relationships with adults may hinder the possibility that mentees develop trust and connection with an assigned mentor (Kobak & Sceery, 1988; Larose, Tarabulsy, & Cyrenne, 2005), whereas socially skilled youths have been found to be more likely to connect with adults (Morison & Masten, 1991; Spencer, 2007a). At the micro‐social level, there is evidence that mentees' family characteristics and perceptions of the match are related to relationship strength (De Wit, DuBois, Erdem, Larose, & Lipman, 2019; Shamblen, Courser, Schweinhart, & Thompson, 2020). At the programme level, the quality of the programme and the support offered to mentors are considered a benchmark for effective mentoring programmes (Herrera & Karcher, 2013; MENTOR, 2015).…”
Section: Relationship Quality In Mentoring Programmesmentioning
confidence: 99%
“…The pool of available mentors may be limited (DuBois et al, 2011) and, when matches are made, half of the mentoring relationships last 6 months or less (Rhodes, 2012). Although studies have identified factors positively associated with length of mentoring relationships, including parent/ guardian approval of the match relationship (Shamblen, 2019) and the presence of shared likes and dislikes between mentor/mentee (Raposa, 2019), little is known about what factors influence the ability to match a youth with a mentor. In our randomized controlled trial of Take Charge!, an emergency department (ED) based, mentor implemented, research-informed violence prevention program for youth with medically attended peer fight-related injuries that partners with one-on-one community-based mentoring agencies, only 50% of intervention youth were successfully matched with a mentor.…”
Section: Introductionmentioning
confidence: 99%